Short-term side effects of BNT162b2 vaccine in primary care settings in Qatar: a retrospective study - Abdeen, Sami; Abed Alah, Muna; Al-Zaidan, Manal; Mohamed Ibrahim, Mohamed Izham; Abdulmajeed, Jazeel; Al-Nuaimi, Asma Ali; Al-Kuwari, Mohamed Ghaith (Frontiers in Public Health, 2024)
Background Despite the established effectiveness of the BNT162b2 Vaccine, the novel technology demands careful safety monitoring. While global studies have explored its safety, local data remains limited and exhibits some variability. This study investigated short-term side effects among BNT162b2 vaccinated individuals in Qatar. Methods A retrospective analysis was conducted using data extracted from the electronic health records of individuals aged 18 or older across 8 primary health centers who received either the first or second dose of the BNT162b2 vaccine during the period from December 23, 2020, to April 24, 2021. The proportions of individuals experiencing short-term side effects after each dose were calculated. Logistic regression and log binomial regression analyses were used to explore associations with the side effects. Results Among 7,764 participants, 5,489 received the first dose and 2,275 the second, with similar demographics between the groups. After the first dose, 5.5% reported at least one local side effect, compared to 3.9% after the second, with a 1.4 times higher incidence after the first dose (RR 1.4, 95% CI 1.14–1.75) compared to the second. Systemic side effects after the second dose were 2.6 times more common than after the first (RR 2.6, 95% CI 2.15–3.14). Gender, nationality, history of prior COVID-19 infection, and obesity were significantly associated with side effects after the first dose, while age, gender, and nationality, were significant factors after the second dose. Conclusion The rates of side effects following the BNT162b2 vaccine in Qatar were relatively low, with age, gender, nationality, previous infection, and obesity identified as significant predictors. These results emphasize the need for tailored vaccination strategies and contributes valuable insights for evidence-based decision-making in ongoing and future vaccination campaigns.